Pengaruh WFH (work from home), stres kerja, dan kompetensi terhadap kinerja pegawai di badan penelitian dan pengembangan Kota Medan selama masa pandemi Covid-19 - Dewi. EM. Sormin; Ronatio Afriani Lumban Tobing; Fenny Krisna Marpaung (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to analyze the effect of WFH (Work From Home), job stress, and competence on employee performance at the Research and Development Agency of Medan City. The method used is descriptive quantitative. The study found that during the Covid-19 pandemic, WFH had a significant effect, but work stress and competence had no significant effect on employee performance.